LEMBAGA KEUANGAN SYARI’AH DI MATA TOKOH AGAMA NON MUSLIM - Hakim, Luqman (Khatulistiwa, 2012)
The emergence of religious-based institutions, be it social or profit oriented in nature, is often suspected of being a threat to other religions because it is feared the presence of these institutions comes with a mission of heresy. It often appears among the community. Therefore, amid the mushrooming Shariah financial institutions either banks or non banks, the researcher would like to find out the response of non-Muslim religious figures toward the Shariah financial institutions.